Genetic diversity of Syagrus cearensis Noblick in natural populations: implications for conservation of genetic resources - Neves, Abidã Gênesis da Silva; Pinheiro, Luciana Gomes; Fajardo, Cristiane Gouvêa; Vieira, Fábio de Almeida (Acta Scientiarum. Biological Sciences, 2022)
The growing extractive activity in forest areas, the inefficient use of management practices combined with the intensification of socioeconomic activities, are the main factors in the loss of biodiversity. In order to reduce environmental impacts, genetic characterization of populations allows to infer about their real situation. Thus, the present study aimed to perform an analysis of the genetic diversity of populations of Syagrus cearensis using ISSR markers. Populations AQU (Aquicultura), MTB (Mata do Bebo) and MOD (Mata Olho d´água) were sampled, totaling 53 individuals. ISSR markers generated a total of 61 loci. The AQU population had the highest polymorphism index (71%), followed by MTB (57%) and MOD (53%). AQU showed the highest index of genetic diversity, compared to the MTB and MOD populations. There was a high and significant genetic differentiation between populations. Bayesian analysis identified the existence of two groups (K = 2). The genetic bottleneck test was significant for the AQU and MOD populations, according to the SMM model. Thus, the populations of genetic diversity index close to the averages found for tropical species with a similar life history. The presence of a genetic bottleneck was detected in populations. The AQU population presented low sharing of genotypes with the others and should be prioritized in conservation activities.